Pemberdayaan Perempuan Melalui Progran Gaspol : Perempuan Pekerja Ojek Online Di Surabaya - Aysyah, Nabila Nur; Kumalasari, Shinta Dwi Febia; Rosyida, Shofia; Widiyarta, Agus (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
The growth of the digital economy has opened up employment opportunities for women as online motorcycle taxi drivers; however, they still face various challenges, such as limited skills, social vulnerability, and a lack of access to capacity-building opportunities. This study aims to analyze the empowerment of women through the GASPOL Program (Movement to Support Online Motorcycle Taxi Workers) for female online motorcycle taxi workers in the city of Surabaya. The study employs a descriptive qualitative approach using George C. Edwards III’s policy implementation theory, which encompasses communication, resources, dispositions, and bureaucratic structure. Data collection techniques include interviews, observations, and documentation, with data analysis following the Miles and Huberman model and source triangulation. The research results indicate that the implementation of the GASPOL Program has been quite successful in supporting the empowerment of female online motorcycle taxi workers in Surabaya. The communication aspect was carried out through community coordinators and WhatsApp groups; resources were supported by professional facilitators and adequate training facilities despite limited budgets; dispositions showed the commitment of implementers and the enthusiasm of participants; and the bureaucratic structure functioned in a fairly coordinated manner. Nevertheless, expanding the reach of information and enhancing the program’s capacity remain necessary so that the program’s benefits can be felt more widely by female online motorcycle taxi workers in the city of Surabaya. Keyword : Women’s Empowerment, Policy Implementation, GASPOL Program, Female Online Motorcycle Taxi Drivers. The growth of the digital economy has opened up employment opportunities for women as online motorcycle taxi drivers; however, they still face various challenges, such as limited skills, social vulnerability, and a lack of access to capacity-building opportunities. This study aims to analyze the empowerment of women through the GASPOL Program (Movement to Support Online Motorcycle Taxi Workers) for female online motorcycle taxi workers in the city of Surabaya. The study employs a descriptive qualitative approach using George C. Edwards III’s policy implementation theory, which encompasses communication, resources, dispositions, and bureaucratic structure. Data collection techniques include interviews, observations, and documentation, with data analysis following the Miles and Huberman model and source triangulation. The research results indicate that the implementation of the GASPOL Program has been quite successful in supporting the empowerment of female online motorcycle taxi workers in Surabaya. The communication aspect was carried out through community coordinators and WhatsApp groups; resources were supported by professional facilitators and adequate training facilities despite limited budgets; dispositions showed the commitment of implementers and the enthusiasm of participants; and the bureaucratic structure functioned in a fairly coordinated manner. Nevertheless, expanding the reach of information and enhancing the program’s capacity remain necessary so that the program’s benefits can be felt more widely by female online motorcycle taxi workers in the city of Surabaya. Keyword : Women’s Empowerment, Policy Implementation, GASPOL Program, Female Online Motorcycle Taxi Drivers.